2013
DOI: 10.1159/000339453
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <b><i>Trans</i></b>-Fatty Acids on Liver Lipid Metabolism in Mice Fed on Diets Showing Different Fatty Acid Composition

Abstract: Aim: Our aim was to investigate the effects of trans-fatty acids (TFA) on liver lipid metabolism in mice fed on experimental diets rich in either oleic or linoleic acid. Methods: Twenty-two male CF1 mice (22.0 ± 0.1 g) were fed with diets rich in corn oil or olive oil, supplemented or not with TFA (0.75 g TFA/100 g diet), for 4 weeks. Changes in triacylglycerol content, the activity and expression of enzymes involved in lipogenesis and fatty acid oxidation were measured. Results: Supplementation of an olive oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 62 publications
0
8
0
3
Order By: Relevance
“…After centrifugation at 100 000 g for 40 min at 4°C, the supernatant fraction was used for the quantification of enzyme activities. Acetyl-CoA carboxylase (ACC, EC 6.4.1.2), FA synthase (FAS, EC 2.3.1.85) and glucose-6 phosphate dehydrogenase (G6PDH, EC 1.1.1.49) activities were measured following a previously used protocol (33) . Enzyme activities were expressed as mU/mg protein, where 1 mU was 1 nmol NADH consumed (ACC), 1 nmol NADPH consumed (FAS) or 1 nmol NADPH produced (G6PDH), per min.…”
Section: Liver Enzyme Activitiesmentioning
confidence: 99%
“…After centrifugation at 100 000 g for 40 min at 4°C, the supernatant fraction was used for the quantification of enzyme activities. Acetyl-CoA carboxylase (ACC, EC 6.4.1.2), FA synthase (FAS, EC 2.3.1.85) and glucose-6 phosphate dehydrogenase (G6PDH, EC 1.1.1.49) activities were measured following a previously used protocol (33) . Enzyme activities were expressed as mU/mg protein, where 1 mU was 1 nmol NADH consumed (ACC), 1 nmol NADPH consumed (FAS) or 1 nmol NADPH produced (G6PDH), per min.…”
Section: Liver Enzyme Activitiesmentioning
confidence: 99%
“…Several studies have associated the accretion of hepatic lipids with changes in these parameters (30)(31)(32) . As previously demonstrated (22) , in mice fed diets containing olive oil as a source of fat and partially substituted with TFA, the exacerbated lipogenesis may be one of the mechanisms responsible for the elevated liver TAG accretion induced by the presence of TFA. Specifically, the increased expression and activity of the lipogenic enzymes associated with the high mRNA levels of SREBP-1a led to an increase in liver TAG content in the Ot group with respect to O.…”
Section: Discussionmentioning
confidence: 69%
“…The increased hepatic Δ9‐desaturase index, expressed by the c 9‐16:1/16:0 and c 9‐18:1/18:0 ratios, in animals fed olive oil diets in both the absence and presence of TFA seems to reflect a raised enzyme activity but not an increase of flux by substrate induction. Thus, dietary olive oil might increase the hepatic relative conversion rate of VA to RA as well as amplify the increased biosynthesis of FA previously observed in animals fed Ot diets and in animals fed olive oil supplemented with RA . Moreover, in agreement with Hurtado de Catalfo et al animals fed olive oil showed an increase of the relative conversion rate of n‐6 and n‐3 LC‐PUFA in liver.…”
Section: Discussionmentioning
confidence: 92%
“…In a previous work, we demonstrated that TFA induced hepatic steatosis in mice fed an olive oil diet but not in those fed a corn oil diet. In addition, differences in lipid metabolic regulation were associated with the consumption of olive oil supplemented with partially hydrogenated vegetable oil (PHVO) . Nevertheless, we did not determine the relation of these metabolic alterations with TFA incorporation and retention in liver.…”
Section: Introductionmentioning
confidence: 99%